Effectiveness of laser welding in cerclage wiring fixation: a biomechanical study - Pengrung, Nachapan; Sa-ngasoongsong, Paphon; Sabsuantang, Konlawat; Thongchuea, Nutchanat; Warinsiriruk, Eakkachai (Frontiers in Surgery, 2023)
Introduction: Cerclage wiring is a common orthopedic procedure for fracture fixation. However, previous studies reported wiring-related perioperative complications, as wire loosening or breakage, with an incidence up to 77%. Recently, the application of laser welding on medical implants was introduced to connect biomedical materials. This study applied laser technology to weld between wires after conventional cerclage fixation. We hypothesized that the laser welding could significantly increase the biomechanical properties of cerclage wiring fixation. Methods: Twenty-five wiring models underwent biomechanical tests in 5 cerclage wiring configurations (5 models per group): (1) single loop, (2) single loop with laser welding, (3) double loop, (4) double loop with one-side laser welding, and (5) double loop with two-side laser welding. Load to failure, mode of failure, and wiring failure characteristics were compared between groups. The biocompatibility for the stainless-steel wire 316L with laser welded was evaluated via an in vitro hemolysis test. Results: Mean load to failure of the double loop with one-side and two-side laser-welding groups were 3,596±346 N and 3,667±240 N, which were significantly higher than for the double loop group (2,919±717 N) (p=0.012 and p=0.044, respectively). Conversely, comparing the mean load to failure between the single loop and single loop with laser-welded cerclage wire showed no significant difference (1,251±72 N., 1,352±122 N., and p=0.12). Untwisted wire and wire breakage were the most common mode of failure. All welding specimens revealed non-hemolytic effects from in vitro hemolysis test. Conclusion: Laser welding on cerclage wiring significantly increases the biomechanical property of double cerclage wire fixation. However, further biocompatibility tests and clinical studies are still recommended.